2016
DOI: 10.1016/j.molcatb.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and heterofunctionalized silica magnetic microparticles (SMMPs) as new carriers for immobilization of lipases

Abstract: a b s t r a c tIn order to improve economic viability of an enzymatic process, the use of an operationally stable and low-cost biocatalyst is encouraged. Although the immobilization of lipases is widely reported, the search for new supports and immobilization protocols with better properties is still important. In this study, mono-and heterofunctionalized silica magnetic microparticles (SMMPs) were synthetized for immobilization of lipase B from Candida antarctica (CALB). The SMMPs were prepared in a micro-emu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Some studies already evaluated the use of molecular sieves in the enzyme-catalyzed synthesis of xylose fatty esters [ 6 , 12 , 27 , 56 ]. Among those authors, Tsukamoto et al [ 56 ] found higher xylose conversions in the presence of MS when compared to the conversions in the absence of them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies already evaluated the use of molecular sieves in the enzyme-catalyzed synthesis of xylose fatty esters [ 6 , 12 , 27 , 56 ]. Among those authors, Tsukamoto et al [ 56 ] found higher xylose conversions in the presence of MS when compared to the conversions in the absence of them.…”
Section: Resultsmentioning
confidence: 99%
“…The interfacial adsorption of lipases on hydrophobic supports [ 24 ], covalent bonds, and ionic interactions are among the immobilization techniques reported in this period [ 25 ]. These methods included the use of different supports, such as chitosan, celite, silica magnetic microparticles, octyl silica [ 26 , 27 , 28 , 29 ], and microemulsion-based organogels (MBGs) [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, immobilized Pseudomonas cepacia lipase onto magnetic nanoparticles (MNPs) was used for ester production from waste cooking oil. Lipase from Rhizomucor miehei immobilized on ion-exchange macroporus hydrophilic resins also used for trans-esterification of waste oil for ester production (de Lima et al 2016).…”
Section: Screening Of Organic Solvent For Ester Productionmentioning
confidence: 99%
“…3.1.1.3) are enzymes whose physiological function is the hydrolysis of triacylglycerols, while in vitro they may be used in the reverse reaction (esterification), as well as transesterification . They are an important group of biocatalysts, with biotechnological applications in many biotransformation reactions in the pharmaceutical, food, and agrochemical industries due to their excellent chemo‐, regio‐ and enantio‐specificities . These enzymes have a peculiar mechanism of catalysis, denominated interfacial activation that permits them to fulfill their physiological function …”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] They are an important group of biocatalysts, with biotechnological applications in many biotransformation reactions in the pharmaceutical, food, and agrochemical industries due to their excellent chemo-, regio-and enantio-specificities. [15][16][17][18][19][20] These Correspondence concerning this article should be addressed to P.W. Tardioli at pwtardioli@ufscar.br and to W. Kopp at solutions@kopptechnologies.com or willkopp@gmail.com enzymes have a peculiar mechanism of catalysis, denominated interfacial activation that permits them to fulfill their physiological function.…”
Section: Introductionmentioning
confidence: 99%